2013
DOI: 10.4236/ojra.2013.33026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-TNF Therapy on Resistance to Insulin in Patients with Rheumatoid Arthritis

Abstract: Objective: To evaluate the effect of anti-TNF therapy on resistance to insulin in patients with rheumatoid arthritis (RA) compared with patients with RA being treated with non-biological DMARDs. Methods: Inactive patients diagnosed with RA (ACR 1987 criteria) (DAS 28 < 2.6) were included, being treated with anti-tumor necrosis factor inhibitors (anti-TNF) (cases) and non-biological disease-modifying anti-rheumatic drugs (DMARD) (controls), without risk factors for insulin resistance (administration of steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The reduction in the HOMA, however, may not be exclusively seen only with TNFi therapy in RA. Cross sectional studies by Perez et al and Cuchacovich et al [ 34 , 35 ] found no difference in the HOMA index between the TNFi arm and the methotrexate (MTX) treated arm. In a recent study by Rajappa et al [ 36 ] systemic MTX therapy was associated with a significant reduction in insulin levels and insulin resistance indices in patients with psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the HOMA, however, may not be exclusively seen only with TNFi therapy in RA. Cross sectional studies by Perez et al and Cuchacovich et al [ 34 , 35 ] found no difference in the HOMA index between the TNFi arm and the methotrexate (MTX) treated arm. In a recent study by Rajappa et al [ 36 ] systemic MTX therapy was associated with a significant reduction in insulin levels and insulin resistance indices in patients with psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 99%